2020
DOI: 10.1055/s-0040-1703422
|View full text |Cite
|
Sign up to set email alerts
|

Platelet and Red Blood Cell Indices in Patients with Panic Disorder: A Receiver Operating Characteristic Analysis

Abstract: Objective Panic disorder (PD) is associated with changes in platelet and red blood cell (RBC) indices. However, the diagnostic or predictive value of these indices is unknown. This study assessed the diagnostic and discriminating value of platelet and RBC indices in patients with PD. Materials and Methods In this cross-sectional study including patients with PD (n = 98) and healthy controls (n = 102), we compared the following blood indices: mean platelet volume (MPV), platelet distribution width (PDW), and RB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Indeed, serotonergic agents have been reported to relieve panic symptoms [ 307 ]. Some of these studies reported evidence of increased MPV in PanDis patients vs. healthy controls [ 177 , 184 , 185 ], while others reported significant associations with an opposite direction of effect [ 168 , 169 , 178 ]. Those works which analyzed PDW reported higher values for cases [ 168 , 169 , 185 ], except for one detecting no significant differences [ 178 ].…”
Section: Mdd Comorbidities and Plateletsmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, serotonergic agents have been reported to relieve panic symptoms [ 307 ]. Some of these studies reported evidence of increased MPV in PanDis patients vs. healthy controls [ 177 , 184 , 185 ], while others reported significant associations with an opposite direction of effect [ 168 , 169 , 178 ]. Those works which analyzed PDW reported higher values for cases [ 168 , 169 , 185 ], except for one detecting no significant differences [ 178 ].…”
Section: Mdd Comorbidities and Plateletsmentioning
confidence: 99%
“…Some of these studies reported evidence of increased MPV in PanDis patients vs. healthy controls [ 177 , 184 , 185 ], while others reported significant associations with an opposite direction of effect [ 168 , 169 , 178 ]. Those works which analyzed PDW reported higher values for cases [ 168 , 169 , 185 ], except for one detecting no significant differences [ 178 ]. Likewise, for Plt, contrasting results were reported: higher count in PanDis patients [ 168 , 169 ] vs. no significant difference between cases and controls in [ 177 , 178 ].…”
Section: Mdd Comorbidities and Plateletsmentioning
confidence: 99%
See 2 more Smart Citations
“…Şizofreni (1), bipolar bozukluk (BB) (3), major depresif bozukluk (MDB) (4) ve madde kullanım bozukluğu (MKB) (5,6), TKS ile ilişkisi sıklıkla araştırılmış psikiyatrik bozukluklardır. Anksiyete bileşeni olan psikiyatrik bozukluklardan panik bozukluk (PB) (7) ve obsesifkompulsif bozukluk (OKB) (8)'deki TKS verilerine de literatür vasıtasıyla ulaşılmaktadır.…”
Section: Introductionunclassified